The Maddela effect designing a sustainable agricultural ecosystem in a campus landscape through ecosystem mimicry - Pizarra, Aydin Juliannah; Villajuan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Despite being known as an agricultural country, the Philippines is struggling with its farming practices. Majority of the farmers still practice monoculture and are hesitant with using modern technology. This has resulted to having agricultural lands that cannot adapt and has become vulnerable to the extreme weather and infestations. An example of this can be the vast agricultural lands that make up majority of the Quirino State University Maddela campus, which is known for its agricultural and vocational courses. This study shows how designing a sustainable agricultural ecosystem can still be cohesive to the goals of its campus. Moreover, this study aims to widen the knowledge on alternative farming practices, specifically on the “ecosystem mimicry” approach, that can be profitable and at the same time sustainable.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Agroforestry; Campus planning; Universities and colleges--Landscape development; Quirino State University--Landscape development